Potensi Ekstrak Metanol Daun Awar-awar (Ficus septica Burm. f.) sebagai Penghambat Aspergillus niger pada Lontar Bali - Julyeda, Ni Komang Deny; Darmayasa, Ida Bagus Gde; Hardini, Junita (Metamorfosa: Journal of Biological Sciences, 2021)
Ficus septica Burm. f. is a wild plant that has antifungal compounds. Exploration of antifungal compounds from natural material important in inhibiting the growth of Aspergillus niger , one of Balinese lontar destructive fungus. Natural material use to reduse lontar damage due to synthetic materials. This study aims to inhibition of awar-awar leaf methanol extract ( in vitro ) . The method used was a complete randomized design with 7 treatments for the concentration of the awar-awar leaf methanolic extract of 10.000, 20.000, 30.000, 40.000, 50.000 ppm (b/v), positive control ( nystatin ), and negative control (methanol). The minimum inhibitory concentration (MIC) test uses 6 treatments for the concentration of the awar-awar leaf methanolic extract of 100, 500, 1000, 2000 ppm (w/v), positive control ( nystatin ), and negative control (methanol). Giving the extract to the diffusion well with potato dextrose agar (PDA) media. The research data were analyzed statistically ANOVA (DMRT with 5% significance level) with the SPSS 23 version for windows. The results showed that the awar-awar leaf methanol extract had MIC at a concentration of 500 ppm (w/v). Concentrations of 10.000-50.000 ppm (w/v) indicate the inhibition zone diameter of 20.50 mm, respectively; 23.00 mm; 23.50 mm; 23.75 mm; 24.75 mm. The concentration of 10.000 ppm (w/v) has higher inhibition than the positive control. The concentration of 20.000 ppm (w/v) was the optimum concentration of inhibition of awar-awar leaf methanol extract. Conclusion of this research was awar-awar leaf methanol extract had anti-fungal compounds which inhibited the growth of A. niger. This extract can be used as an alternative to inhibit the growth of fungi that cause lontar damage. Keyword: Aspergillus niger , destructive fungi, Ficus septica Burm. f.